Romance and sex in adolescence and emerging adulthood : risks and opportunities - Crouter, Ann C.; Booth, Alan, 1935-2015 (Penn State University family issues symposia series., 2006)
Examines the nature and origin of adolescents' contemporary patterns of sexual and romantic relationships, spanning such diverse topics as the evolutionary roots of these behaviors. This book is useful for academicians and upper-lever undergraduate and graduate students in the fields of human development and family studies and psychology.